Literasi Keuangan Syariah: Solusi Tepat Mencegah Jerat Judi Online dan Pinjaman Online Ilegal (Lembaga Pengembangan Kinerja Dosen, 2025)
The proliferation of Online Gambling (Judol) and Illegal Online Loans (Pinjol) poses a serious threat to the financial stability and morality of society, particularly among the youth. The high number of detected illegal entities necessitates fundamental educational intervention. The objective of this community service project is to equip students with an in-depth understanding of the dangers posed by these two illegal practices and to enhance their Sharia Financial Literacy as an ethical defense mechanism based on Islamic law. The methodology employed was an interactive and educational training session held at SMP Syubbanul Wathon Tegalrejo on November 15, 2024. The service material included a description of Judol and Pinjol, an analysis of addiction factors, and solutions guided by Sharia principles. The results demonstrate that understanding Sharia principles effectively provides an ethical framework for financial decision-making. Participants were equipped with practical skills to verify the legality of online loans with the Financial Services Authority (OJK), manage financial stress, and shift negative behavior towards positive activities.